(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Studies on atmospheric thermal balancing, atmospheric radiative transmission, and the assessment and design of solar energy systems all depend on an accurate estimate of the Earth’s albedo. This study compared the variability in albedo for two locations, Owerri and Ikeja distributed over Nigeria’s coastline climatic regions, using monthly average daily observed meteorological data on global solar radiation alongside wind speed, mean temperature, surface pressure and relative humidity over thirty-nine-year period (1984-2022) from the National Aeronautics and Space Administration (NASA). 11 models in all, divided into three groups, were derived from regression models with two, three, and four variables were developed and tested using five validation indices of Mean Bias Error (MBE), Root Mean Square Error (RMSE), Mean Percentage Error (MPE), t-test and coefficient of determination (R2). All the developed models that stood out the most were ranked according to their suitability for estimating surface albedo. For Owerri, the three-variable regression model which relates wind speed, relative humidity and mean temperature, ALB7 (Eqn. 26g) performed best, while the two variable regression model which relates the relative humidity and mean temperature, ALB15 (Eqn. 27d) performed best for estimating surface albedo for Ikeja. The Earth’s emitted surface temperature for Owerri ranged from 219.1845 K in August to 239.6133 K in January, while for Ikeja it varies from 221.4955 K in August to 238.7534 K in November. The longwave radiation at both locations is in the infrared part of the electromagnetic spectrum, as indicated by the maximum emission wavelength values.